The Principle of Freedom of Contract in Insurance Agreements Who Are Not the Heirs - Fikri Haikal Den Pratama; Mhd. Fakhry Jaidan; Dian Perwita Sari; Hasniyarti Putri; Andi Muhammad Yusuf Adhyaksa Konggoasa (Jurnal Sahabat ISNU SU, 2024)
The principle of freedom of contract grants parties the autonomy to determine the terms and conditions of an agreement, including the designation of insurance beneficiaries. However, the appointment of third parties who are not legal heirs as beneficiaries often raises legal uncertainty and challenges regarding consumer protection. This study aims to analyze the application of the principle of freedom of contract in insurance agreements involving non-heir third-party beneficiaries and to examine its implications for consumer legal protection under Indonesian law. This research employs a normative legal research method using statutory, conceptual, and case approaches. The study relies on primary, secondary, and tertiary legal materials, which are analyzed qualitatively through legal interpretation and legal reasoning. The findings indicate that the principle of freedom of contract permits the designation of non-heir beneficiaries, provided that the agreement complies with the requirements of a valid contract, the principle of insurable interest, and the principle of good faith. Nevertheless, the use of standard clauses and the absence of explicit legal provisions governing third-party rights often create legal uncertainty and weaken consumer protection. Therefore, stronger regulatory oversight, greater contractual transparency, and clearer recognition of third-party rights are essential to ensuring legal certainty and balancing contractual freedom with consumer protection in insurance agreements. This study contributes to the development of Indonesian insurance law by emphasizing the need to harmonize contractual autonomy with legal safeguards for all parties involved.